2020
DOI: 10.2147/cia.s286007
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Compliance with an Enhanced Recovery After Surgery Program on the Outcomes Among Elderly Patients Undergoing Lumbar Fusion Surgery

Abstract: Background and Aim The benefits of the enhanced recovery after surgery (ERAS) program to elderly patients have not been evaluated in lumbar fusion surgery. Compliance with the ERAS program is associated with prognosis. There is currently no adequate assessment about the importance of the individual components of ERAS program in lumbar fusion surgery. The aim of the study was to analyze the effect of compliance with our ERAS program and the relative importance of the individual ERAS program compone… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1
1

Relationship

4
6

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 30 publications
0
23
0
Order By: Relevance
“…Nevertheless, the implementation of the ERAS protocol in orthopedic practice remains a difficult issue [ 7 ]. Recently, a number of studies on ERAS have reported various obstacles in ERAS implementation, such as reduced compliance and ERAS protocol deviation by providers and patients [ 8 , 9 ]. To transfer the ERAS protocol to be practiced successfully, practical strategies based on a sufficient understanding of ERAS components and their outcomes are necessary.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, the implementation of the ERAS protocol in orthopedic practice remains a difficult issue [ 7 ]. Recently, a number of studies on ERAS have reported various obstacles in ERAS implementation, such as reduced compliance and ERAS protocol deviation by providers and patients [ 8 , 9 ]. To transfer the ERAS protocol to be practiced successfully, practical strategies based on a sufficient understanding of ERAS components and their outcomes are necessary.…”
Section: Introductionmentioning
confidence: 99%
“…In an effort to improve our perioperative care, ERAS was considered in January 2018 and implemented in January 2019. 16 To increase the reliability of the data, we selected two periods, pre-ERAS (from January to December, 2017, n = 54) and ERAS (from January to December, 2020, n = 46) and the ERAS group was treated with standard ERAS items while the pre-ERAS group was performed with no unified guidelines. We enrolled patients over 75 years of age, diagnosed with lumbar disc herniation or lumbar spinal stenosis and underwent polysegement fusion surgery, defined as more than two fusion levels.…”
Section: Methodsmentioning
confidence: 99%
“…And all of these patients strictly followed the same discharge criteria published by our department previously: no clinical complications; visual analog scales < 3 with oral analgesics; independent ambulation or ambulation with minimal assistance; absence of fever in the last 48 hours. 14 The collected preoperative clinical data included age, sex, body mass index (BMI), smoking status, concomitant diseases, American Society of Anesthesiologists (ASA) grade, preoperative albumin, and hemoglobin levels, operation time, anesthesia time, estimated blood loss (EBL), and need for allogenic transfusion. Postoperative complications (nausea and vomiting, electrolyte imbalance, urinary retention, deep venous thrombosis, postoperative hypoproteinemia, surgical site infection, and myocardial ischemia), LOS, urinary catheter extraction time, and mobilization time were also extracted.…”
Section: Methodsmentioning
confidence: 99%